Interpreting early India - Romila Thapar 1931 - (Oxford University Press, 1992)
"The essays in this volume are centrally about the ways in which early Indian history has been interpreted. More generally, they focus on issues in social history." "Professor Thapar argues the importance of understanding and positioning various well-established perspectives on the Indian past in order to arrive at an informed understanding of contemporary situations - such as disputes between Hindus and other Indian communities. It is vitally important for historians and informed lay readers to consider the wide range of opinions and views that are available on our past, particularly on religion and society in ancient India." "Interpretations rise out of ideological conceptions. Professor Thapar shows that the most influential ideologies which shaped the writing of early India initially had their moorings in European concerns; later, the rise of Indian nationalism questioned many of these conceptions; and most recently, these nationalist interpretations have also been questioned." "This volume has essays on Durkheim and Weber's views on Indian caste and society; on D.D. Kosambi's contribution to Indian historiography; and on the recent attempts to project a composite Hinduism in early India by ignoring evidence on the existence of multiple communities and diverse identities." "Romila Thapar was Professor of Ancient Indian History at Jawaharlal Nehru University."--BOOK JACKET.